Relationships among Achievement Emotions, Mathematical Problem-Solving Beliefs, and Metacognition in Indonesian High School Students - Rafiq Zulkarnain; Gida Kadarisma (Journal of Honai Math, 2025)
Mathematics learning is influenced not only by cognitive factors but also by affective components such as emotions, beliefs, and metacognition. However, limited research has explored how achievement emotions interact with mathematical problem-solving beliefs and metacognition, particularly among Indonesian students. This study examine the relationships between achievement emotions, mathematical problem-solving beliefs, and metacognition in 750 Indonesian high school students from 10th and 11th grades. The Participants completed questionnaires measuring achievement emotions (in classroom and test contexts), mathematical problem-solving beliefs, and metacognitive components awareness, cognitive strategies, planning, and self-checking. The findings demonstrated substantial associations among these elements: positive emotions, particularly enjoyment and pride, reinforced both problem-solving beliefs and metacognition, while negative emotions like anxiety and anger impaired them during mathematical problem-solving tasks. The outcomes emphasize the critical role of developing positive emotions such as enjoyment and pride while diminishing negative emotions, particularly anxiety, in enhancing students' metacognitive skills and mathematical problem-solving performance. In addition, this study supports the Control-Value Theory of Achievement Emotions by empirically validating that mathematical problem-solving beliefs act as intermediaries between emotions and metacognitive processes.  This contribution offers new theoretical insight into how affective factors shape higher-order cognitive regulation, providing a novel understanding of the emotional foundations of mathematics learning in the Indonesian context. These findings emphasize the importance of emotions in shaping students' engagement with mathematics and highlight the need for teaching strategies that promote emotional well-being alongside cognitive development.